Tetraplex real-time PCR with TaqMan probes for discriminatory detection of cat, rabbit, rat and squirrel DNA in food products - Ahamad, Mohammad Nasir Uddin; Hossain, M.A. Motalib; Uddin, Syed Muhammad Kamal; Sultana, Sharmin; Ahmad Nizar, Nina Naquiah; Bonny, Sharmin Quazi; Johan, Mohd Rafie; Ali, Md. Eaqub (Springer, 2019)
Cat, rabbit, rat, and squirrel species are very sensitive in food products because most of them are potential carriers of zoonotic diseases and rejected in most religions and cultures. Since cats and rats are abundant in most parts of the world and their meats do not carry any value in legal markets, these meats could be considered as potential adulterants in halal, kosher, and other food markets. Rabbit and squirrel meats are also susceptible to adulteration. Therefore, both health and economic interests in rat, rabbit, cat and squirrel species are significant. In this work, a novel tetraplex real-time PCR assay with TaqMan probes was described to discriminate and identify all four species (cat, rabbit, rat, and squirrel) in a single assay platform. Species-specific primers and probes were developed against ATP6, and cytochrome b genes to amplify 108, 123, 161 and 176 bp DNA fragments from rat, rabbit, squirrel and cat meat products under various states. A 141-bp internal amplification control (IAC) of 18S rRNA was used to avoid any false-negative results. Specificity was evaluated against 22 species but no cross-reactivity was found. Efficiency of PCR assay as well as target quantification were determined based on a standard curve that was generated using tenfold serially diluted mixed DNA extract (1:1:1:1) from squirrel, rat, rabbit and cat species. The assay was valid under pure, processed and admixed states with 10–0.1% (w/w) adulterant from each species. The limit of detection was 0.1% under admixed samples and 0.003 ng DNA under pure states from each species. Analyses of 18 model burgers (9 chicken and 9 beef) and 18 frankfurters (9 chicken and 9 beef) revealed 91–122% target recovery at 0.1–10% adulteration. Finally, 72 commercial burgers (36 chicken and 36 beef) and 72 frankfurters (36 chicken and 36 beef) were screened but no target species was detected except IAC. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.